Factores socioeconómicos y culturales Relacionados con la participación de los varones En el programa de planificación familiar en el Centro de salud punta del este. Agosto-noviembre 2015 - Pinchi Del Águila, Avency (2015)
This research study aims to determine the relationship between Socioeconomic and cultural factors and the involvement of men in family Planning program; whose population was 79 males. Quantitative, descriptive, Prospective cross-sectional study, the data collection technique was the survey And a questionnaire as an instrument was used. The results were: the involvement of men in family planning program is regular In 75.9%, their age ranging from 19 to 30 years, 81.0% also stated that to the Property of Health take less 30 minutes, 44% have completed secondary Education; most are workers or farmers, traders, public / private Employees; and the income is 750 and 1500 soles; 74.7% are Catholics, choice Of contraceptive method is carried out by both the majority; the preferred Method of contraception is the condom. In conclusion there is a significant relationship between social factors And the involvement of men in family planning program through time to get to Hospital, level of education and interpersonal relationships, however there is X No significant relationship with cultural, economic and the involvement of Men in family planning program.